2022
DOI: 10.14444/8232
|View full text |Cite
|
Sign up to set email alerts
|

Single-Position Anterior Column Lateral Lumbar Interbody Fusion

Abstract: Lateral lumbar fusion is a commonly used spinal fusion technique that allows for indirect neural decompression while correcting sagittal malalignment. The lateral position has evolved to include placement of percutaneous pedicle screw fixation, anterior longitudinal ligament release, and approach the L5-S1 segment. This review article focuses on the anatomy and technique of the single-position anterior column spinal fusion and highlights the recent trends, outcomes, and future directions for the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…P-SPS overcomes the aforementioned downsides of L-SPS, being procedurally similar to L-SPS, except that the patient is placed in a prone position instead of laterally ( Figure 4 ). This positioning offers a more familiar and spacious area for the surgeon to operate, facilitating easier pedicle screw placement and posterior decompression, as deemed necessary [ 151 , 152 , 153 ]. Furthermore, studies have demonstrated that adopting a prone position enables enhanced correction of sagittal plane imbalance attributed to an augmented lumbar lordosis [ 148 , 154 ], resulting in better segmental lordosis correction when compared to L-SPS ( Table 4 ) [ 155 ].…”
Section: Recent Advancesmentioning
confidence: 99%
“…P-SPS overcomes the aforementioned downsides of L-SPS, being procedurally similar to L-SPS, except that the patient is placed in a prone position instead of laterally ( Figure 4 ). This positioning offers a more familiar and spacious area for the surgeon to operate, facilitating easier pedicle screw placement and posterior decompression, as deemed necessary [ 151 , 152 , 153 ]. Furthermore, studies have demonstrated that adopting a prone position enables enhanced correction of sagittal plane imbalance attributed to an augmented lumbar lordosis [ 148 , 154 ], resulting in better segmental lordosis correction when compared to L-SPS ( Table 4 ) [ 155 ].…”
Section: Recent Advancesmentioning
confidence: 99%
“…Although promising, this approach has several disadvantages. One example is the inability to reach the anterior column at L5-S1 without repositioning, as can be achieved with a lateral ALIF approach while in the lateral decubitus position [ 14 ]. An additional disadvantage secondary to positioning is that the spine cannot easily be laterally flexed in order to enlarge the distance between the caudal ribs and the iliac crest, as is performed in lateral decubitus, although this potential drawback can be partially overcome by specially designed patient positioners.…”
Section: The Prone Lateral Approachmentioning
confidence: 99%
“…The desire to perform lateral as well as posterior procedures whilst maintaining an efficient surgical workflow has brought about different methods of single-position dual-approach surgery. The lateral decubitus single-approach position has been described as a feasible option for lateral interbody fusion as well as posterior instrumentation without the need for patient repositioning [ 14 ]. In the lateral position, the anterior column is accessible along the entire length of the lumbar spine, including L5-S1, through ALIF and transpsoas approaches.…”
Section: Introductionmentioning
confidence: 99%